Decreased Concentration (BOD, COD, TSS, Fatty Oil, Ammonia and Coliform) Hospital Wastewater Using Microfiltration Membranes - Santosa, Imam (Jurnal Kesehatan, 2023)
Microfiltration membranes are a technological alternative to the biological method; apart from being easier to operate, they can also be made portable, especially in emergencies such as natural disasters. The problem with the operation of this microfiltration membrane is that saturation occurs quickly on the surface of the microfiltration membrane. It can reduce the efficiency of treatment and the quality of wastewater. This study aimed to determine the initial rate of hospital wastewater and the efficiency of reducing the parameters of hospital wastewater using microfiltration membrane filtration. The research method used is quasi-experimental, which aims to explain things that will happen to the research variables by manipulating and controlling the variables so that the influence of one or more variables is found. The conclusion obtained from this study was the initial hospital wastewater quality in the first hour, namely pH 6.5, BOD 82mg/l, COD 271mg/l, TSS 38mg/l, Fatty Oil 1mg/l, NH3 16mg/l, and Total Coliform 3,400 Total/100ml sample. The quality of the treated wastewater produced by microfiltration membranes was pH 7, BOD 10mg/l, COD 64mg/l, TSS 12mg/l, Fatty Oil 0.5mg/l, NH3 1mg/l, and Total Coliform 800 Total/100ml sample. The efficiency of reducing the concentration of wastewater in all parameters meets the smell of hospital wastewater quality. Suggestions from this study are the installation of a field-scale microfiltration membrane device.